2021
DOI: 10.1002/aet2.10568
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the emergency department: Effects of COVID‐19 on emergency medicine resident education

Abstract: Background: In December 2019, a novel coronavirus (COVID-19) caused widespread clinical disease, triggering limited in-person gatherings and social-distancing guidelines to minimize transmission. These regulations led most emergency medicine (EM)residency training programs to rapidly transition to virtual didactics. We sought to evaluate EM resident perceptions of the effects of COVID-19 on their didactic and clinical education.Methods: We performed a cross-sectional survey study at seven EM residency programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
(23 reference statements)
5
20
0
Order By: Relevance
“…Additionally, residents felt that it was easier to access supplemental resources. These findings align with previously published work citing increased convenience and flexibility of virtual didactics in EM education as well as its drawbacks of lack of social interactions, significant reduction of hands‐on learning opportunities, and decreased engagement 10 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, residents felt that it was easier to access supplemental resources. These findings align with previously published work citing increased convenience and flexibility of virtual didactics in EM education as well as its drawbacks of lack of social interactions, significant reduction of hands‐on learning opportunities, and decreased engagement 10 …”
Section: Discussionsupporting
confidence: 91%
“…These findings align with previously published work citing increased convenience and flexibility of virtual didactics in EM education as well as its drawbacks of lack of social interactions, significant reduction of hands-on learning opportunities, and decreased engagement. 10 Distractions were perceived to be higher in the virtual format.…”
Section: Discussionmentioning
confidence: 96%
“…Hallway medicine disappeared and consultants were 'at the ready'. Similar to other studies, our physicians reported colleagues 17 and members of the public were respectful and thankful. 18 However, the positive impacts on physician mental health were short lived and the overall sense was that participants had experienced negative mental health during the early pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…COVID‐19 is a topic that has become extremely relevant to our clinical practice and was rapidly integrated into the podcasts despite not being part of the MCPEM or ABEM board examination coverage. While this demonstrates a potential benefit for access to time‐sensitive and rapidly changing information, research has shown that this may be disproportionately covered in resident education 12 . While it remains unclear what would be disproportionate coverage in podcasts, future research should compare this with the MPCEM and ABEM examination as well as to evaluate the impact of this on coverage of other topics.…”
Section: Discussionmentioning
confidence: 99%